Agricultural adaptation to climate change in Africa : food security in a changing environment - Berck, Cyndi Spindell, |e editor; Berck, Peter, |d 1950- |e editor; Di Falco, Salvatore, |e editor (Environment for development book series, 2018)
A changing climate is likely to have a drastic impact on crop yileds in Africa. The focus is on Sub-Sharan Africa, an area that is already affected by changing pattern of heat and rainfall. Because teh high prevalence of Subsistence farming, food insecurity, and extremepoverty in this region.The book includes empirical research in Ethopia, Kenya, South Africa, Tanzania anda othe Sub-Saharan countries and conclusion summarizes policy relevant findings from chapters. The purpose of this book is to document the effects of climate change on agriculture in Africa and to discuss strategies for adaption to hotter weather and less predictable rainfall. The strategies include promoting oppurtunities for farmers to adopt technologies that produce optimal result in terms of crop yiled and income under localagro-ecological and socioeconomic condition.